Inequality in Personality over the Life Cycle - Miriam Gensowski; Mette Gørtz; Stefanie Schurer (Institute of Labor Economics (IZA), 2020)
We describe gender and socioeconomic inequalities in the Big Five personality traits over the life cycle, using a facet-level inventory linked to administrative data. We estimate life-cycle profiles non-parametrically and test for cohort and sample-selection effects. We discuss the economic implications of the following findings: Women of all ages score more highly than men on all personality traits, including three that are positively associated with wages; Individuals with high own or parental education have more favorable traits except Conscientiousness; Over the life cycle, gender and socioeconomic gaps widen in Openness and shrink in Neuroticism, a trait associated with worse outcomes.
Keywords: J24; I24; J62; I31; J16; 330; inequality; socio-emotional skills; personality traits; Big Five facets; life cycle dynamics; gender gap; intergenerational transmission